2012
DOI: 10.1371/journal.pone.0044924
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Microendoscopy for the Detection of Cervical Neoplasia in Low-Resource Settings

Abstract: Cervical cancer is the second leading cause of cancer death among women in developing countries. Developing countries often lack infrastructure, cytotechnologists, and pathologists necessary to implement current screening tools. Due to their low cost and ease of interpretation at the point-of-care, optical imaging technologies may serve as an appropriate solution for cervical cancer screening in low resource settings. We have developed a high-resolution optical imaging system, the High Resolution Microendoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 17 publications
1
62
0
Order By: Relevance
“…Normal squamous epithelium is characterized by regularly spaced, small nuclei. In contrast, the area of HSIL showed larger, more closely spaced nuclei, which is consistent with previous studies using high resolution microendoscopy to study squamous epithelium where increased nuclear density and nuclear size are observed and can be quantified in dysplastic tissue (13,14,31). The DSIMe images corresponding to the HSIL region showed improved image contrast.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Normal squamous epithelium is characterized by regularly spaced, small nuclei. In contrast, the area of HSIL showed larger, more closely spaced nuclei, which is consistent with previous studies using high resolution microendoscopy to study squamous epithelium where increased nuclear density and nuclear size are observed and can be quantified in dysplastic tissue (13,14,31). The DSIMe images corresponding to the HSIL region showed improved image contrast.…”
Section: Resultssupporting
confidence: 90%
“…Improvements in image contrast enable improved recognition of nuclear morphometry, particularly in areas of precancer and cancer. Although visually compelling, the improved nuclear recognition could also improve automated algorithms designed to identify neoplasia in real time that would otherwise struggle in highly scattering tissue (14,32,33). Additionally, because DSIMe maintains the small size of the probe, this technique could be used to improve high resolution microendoscopy imaging in a wider array of tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phantoms were designed to simulate fluorescently labeled nuclei distributed at varying depths within scattering tissue, mimicking the proflavine-stained epithelium imaged in earlier HRME studies. The HRME has no optical sectioning ability with which to eliminate out-of-focus light when imaging thick tissue, but nevertheless can clearly delineate epithelial nuclei in normal and neoplastic tissues [26][27][28]. We showed here that the HRME system produces images of deep lying (defocused) objects with apparent diameters as predicted by a simple geometric model.…”
Section: Discussionmentioning
confidence: 86%
“…The simplicity, low cost, and real-time imaging performance of the HRME system have led to its use by several research groups in laboratory studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24] and in vivo clinical investigations [25][26][27][28]. However, the imaging properties of the HRME system have not been fully characterized; in particular, the axial imaging range and sensitivity to out-of-focus light have to the best of our knowledge, not been quantitatively studied.…”
Section: Introductionmentioning
confidence: 99%